Pengembangan Lembar Kerja Siswa dengan Macromedia Flash pada Pembelajaran Teks Eksplanasi Berbasis Ekologi Siswa Kelas VIII SMPN 3 Penukal Utara - VENDRA ARDIANSYAH (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2023)
Abstract: This study aims to produce teaching materials in the form of worksheets using Macromedia flash in teaching ecological-based explanatory texts that can be used by teachers and students at SMPN 3 Penukal Utara. This research is research and development (Research and Development) which collaborates the Jolly and Bolitho development model and the Dick, Carey, and Carey development model into eight steps, namely: (1) identification of teaching material needs, (2) exploration of material needs, (3 ) contextual realization, (4) pedagogic realization, (5) production of teaching materials, (6) expert validation, (7) revising learning, and (8) designing and conducting formative evaluations. The developed LKS prototype consists of a start page, instructions for use, teaching materials, KI & KD, objectives, concept maps, and materials. To find out the validity, practicality, and potential effects of the worksheets that have been developed, validation tests were carried out by experts/experts, and three stages of formative evaluation using questionnaires, interviews, and tests. Based on the validation results of three aspects (appropriateness of content/material substance, language, presentation, and graphics), worksheets are categorized as good or valid. Based on the practicality test through one-to-one evaluation and small group evaluation, the LKS is categorized as very good or very practical. From the results of field trials (field trials) through pretest and posttest, there was an increase in the average student score of 30.25 so that the LKS could be categorized as effective for students. Keywords: LKS Development; Macromedia Flash; Explanatory Text, Students